Reseña de: Chris EALHAM y Michael RICHARDS (eds.) The splintering of Spain. Cultural History and the Spanish Civil War, 1936-1939, Cambridge, Cambridge University Press, 2005 - Rodrigo, Javier (Historia del Presente, 2007)
-